2C or not 2C? - Céline Guivarch; Stéphane Hallegatte (Fondazione Eni Enrico Mattei (FEEM), 2011)
Political attention has increasingly focused on limiting warming to 2êC. However, to date the only mitigation commitments accompanying this target are the so-called Copenhagen pledges, and these pledges appear to be inconsistent with the 2êC objective. Diverging opinions on whether this inconsistency can or should be resolved have been expressed. This paper clarifies the alternative assumptions underlying these diverging view points and explicits their implications. It first gives simple visualizations of the challenge posed by the 2êC target. It then proposes a decision tree, linking different beliefs on climate change, the achievability of different policies, and current international policy dynamics to various options to move forward on climate change.
Keywords: Q5; Q58; 330; Feasibility of 2êC Target; Climate Change Negotiations